2004
DOI: 10.1097/00000478-200404000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Expression Patterns of Germinal Center and Activation B-cell Markers Correlate With Prognosis in Diffuse Large B-cell Lymphoma

Abstract: Recent studies with cDNA microarrays showed that diffuse large B-cell lymphoma (DLBCL) cases with gene expression profiles similar to germinal center (GC) B cells had much better prognosis than DLBCL cases with gene expression profiles resembling activated B cells. The goal of the current study is to evaluate if using a panel of GC B-cell (CD10 and Bcl-6) and activation (MUM1/IRF4 and CD138) markers by immunohistochemistry defines prognosis in patients with de novo DLBCL. Immunohistochemical stains for the abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

27
226
5
7

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(266 citation statements)
references
References 36 publications
27
226
5
7
Order By: Relevance
“…Using two-dimensional contour plots, the non-AIDS diffuse large B-cell lymphomas clustered into distinct germinal center and activated B-cell types similar to reports by others. 1, 3,4 We found significant correlation between the germinal center and nongerminal center groups (defined using the three immunostain method described by Hans et al 3 ) and the germinal center and activated B-cell clusters using two-dimensional contour plots, which further validates this new method. We report the new observation that the AIDS-related diffuse large B-cell lymphomas formed a single cluster with an intermediate germinal center activated B-cell phenotype, suggesting a unique pathophysiology.…”
Section: Aids and Non-aids Diffuse Large B-cell Lymphoma R Madan Et Alsupporting
confidence: 66%
See 1 more Smart Citation
“…Using two-dimensional contour plots, the non-AIDS diffuse large B-cell lymphomas clustered into distinct germinal center and activated B-cell types similar to reports by others. 1, 3,4 We found significant correlation between the germinal center and nongerminal center groups (defined using the three immunostain method described by Hans et al 3 ) and the germinal center and activated B-cell clusters using two-dimensional contour plots, which further validates this new method. We report the new observation that the AIDS-related diffuse large B-cell lymphomas formed a single cluster with an intermediate germinal center activated B-cell phenotype, suggesting a unique pathophysiology.…”
Section: Aids and Non-aids Diffuse Large B-cell Lymphoma R Madan Et Alsupporting
confidence: 66%
“…18 Later, it was shown that only three (CD10, BCL6, MUM1) or four (CD10, BCL6, CD138, MUM1) protein markers could accurately predict overall survival. 3,4 Additionally, the expression of the winged helix transcription factor Forkhead box-P1 has been shown to identify a subgroup of patients with especially poor prognosis among the non-germinal center type diffuse large B-cell lymphomas. 19 Prior to the introduction of highly active antiretroviral therapy, the incidence of AIDS-related non-Hodgkin's lymphomas was 60-200 times more frequent in AIDS patients compared to immunocompetent individuals.…”
Section: Aids and Non-aids Diffuse Large B-cell Lymphoma R Madan Et Almentioning
confidence: 99%
“…In the multivariate survival analysis, older age, the presence of B-symptoms, abnormal serum LDH, more advanced clinical stage (III/IV), and TIMP-1 expression were related to poorer overall survival in the patients with diffuse large B-cell lymphoma. This result is in agreement with those of previous studies of diffuse large B-cell lymphoma using tissue microarray, [59][60][61][62] reflecting the reliability and robustness of our data. Therefore, TIMP-1 expression is an independent factor, and represents a marker for poor prognosis with potential therapeutic implications.…”
Section: Discussionsupporting
confidence: 93%
“…Within the nongerminal center B-cell-like subgroup of DLBCL, bcl-2 expression is associated with a significantly worse overall survival and event-free survival, whereas bcl-2 expression is not predictive of survival within the germinal center B-cell-like subgroup. 23,43,44 Similarly, MUM1 has been reported to be associated with worse overall survival by some investigators, 23,43,44 but was not found to be predictive by others. 42 Uniform high expression of FoxP1 has been associated with a poor outcome.…”
Section: Discussionmentioning
confidence: 95%